PENATALAKSANAAN FISIOTERAPI DENGAN ELECTRICAL STIMULATION (ES), LASER, MASSAGE, DAN MIRROR EXERCISE PADA BELL’S PALSY SINISTRA - Kristoforus Joanino Najong; Zainal Abidin (Bajang Institute, 2025)
Background: Bell's Palsy (BP) is the most common cause of unilateral facial paralysis worldwide. It is an acute peripheral facial nerve paralysis of unknown etiology. All cases of peripheral facial nerve paralysis without a known cause are referred to as Bell's Palsy, a term coined by Sir Charles Bell in 1821 after studying several patients with asymmetric faces. Bell's Palsy is very common globally. Objective: To determine the effects of physiotherapy management using Electrical Stimulation (ES), Laser, Massage, and Mirror Exercise modalities on left-sided Bell's Palsy. Results: Physiotherapy treatment with electrical stimulation (ES), laser, massage, and mirror exercises for Bell's palsy sinistra was carried out in accordance with physiotherapy SOPs, resulting in a reduction in pain, increased muscle strength on the sinistra side of the face, and improved functional ability on the sinistra side of the face Conclusion: Physiotherapy modalities including Electrical Stimulation (ES), Laser, Massage, and Mirror Exercise have been applied to a patient with left-sided Bell's Palsy. After four therapy sessions, there was a significant improvement in facial functional ability, including the presence of muscle contractions during forehead frowning, eyebrow raising, eye closure, and whistling, indicating enhanced facial muscle strength